Flight-initiation-distance in garden eels (Gorgasia sillneri) - Lena Yunger; Yarden Hevroni Sabbah; Reuven Yosef (Discover Conservation)
Abstract This study investigates the impact of ecotourism on the behavior of garden eels (Gorgasia sillneri) in Eilat, Israel, by examining how diver proximity affects their Flight Initiation Distance (FID). We conducted observations at two sites with differing diving activity: Ben Harush Beach (high activity) and Diver’s Village Beach (low activity). Using a GoPro camera, we recorded FID during normal conditions and an eutrophication event characterized by increased organic material. Our results indicate that FIDs were significantly shorter in areas with higher diving activity, with average FIDs of 2.8 m at Ben Harush and 2.1 m at Diver’s Village during eutrophication. These findings suggest that garden eels habituate to human presence, prioritizing foraging over retreating from divers when food is abundant. The study underscores the need for sustainable dive management practices to mitigate the ecological impacts of recreational diving on marine species.